Inflammatory discoveries two years after acute severe COVID-19: a longitudinal biomarker profile assessment in long COVID individuals in the Brazilian Amazon - Maciel, Alex Bezerra Silva; Pinto, Arlene Santos; Maia Silva, Bernardo; Goulart, Cassia Luz; Silva, Luis Felipe Alho; Chaves, Amanda Silva; Mouta, Gabriel Santos; Sato, Camila Miriam Suemi; Valente, Jefferson; Mwangi, Victor Irungu; de Melo, Gisely Cardoso; Monteiro, Wuelton; et al. (Frontiers in Immunology, 2024)
BackgroundIn SARS-CoV-2 infection, cytokines and laboratory biomarkers play a key role in disease progression and their long-term levels have been associated with the outcome of long COVID-19.ObjectivesI) study the levels of cytokines, hematological and biochemical biomarkers in the acute and post-acute phases of COVID-19 disease; and II) assess the impact of COVID-19 vaccine doses on fatigue symptoms.MethodsThis study is an exploratory cohort nested within a clinical and laboratory follow-up of surviving participants after pre-vaccine acute COVID-19 infection with severe clinical manifestations. We analyzed the inflammatory biomarker profiles of fifty SARS-Cov-2 negative healthy controls from before the COVID-19 pandemic, and eighty patients in the acute phase (Day 1, Day 7 and Day 14), and during 4 months and 2 years after hospitalization.ResultsFour months after hospitalization, 91.3% (73/80) of patients exhibited onset of long COVID symptoms, which persisted in 63.7% (51/80) after 2 years. Comparing the baseline values of the cytokines in the controls versus the follow-up times, the cytokines IL-6, IL-8 and IL-10 were high in the acute phase, declining over time after the individual’s recovery, while IL-1β showed an inverse variation, remaining high after 2 years. IL-1β, IL-10, and TNF increased over time post-acute infection, indicating a long-term inflammatory response. Vaccination with four doses, compared to three doses, showed a slight protective effect against fatigue symptoms in the male population (IRR 0.48, 95% CI 0.22 - 1.02; p=0.054). Neutrophil and leukocyte counts showed a significant reduction 2 years after hospitalization. However, platelet count was the laboratory biomarker that best reflects the prediction of long COVID symptoms up for to 2 years.ConclusionAlthough the frequency of long COVID symptoms declines over time after the acute illness, symptoms continue to persist 2 years after hospital discharge. Vaccination with a fourth dose booster appears to significantly influence reduction of symptoms associated with long COVID fatigue among the males. We further identified important laboratory biomarkers for long COVID. Elevated levels of IL-1β, IL-10, and TNF, along with low levels of IL-6, IL-18, and IL-12p70, also offer new insights into the inflammatory state in long COVID.